Keine Erholung der westgrönländischen Grundfischbestände - Rätz, Hans-Joachim (1995)
Since 1991, the aggregate biomass of fish stocks inhabiting the West Greenland shelf stagnates at the lowest level. The latest survey results of cruise no. 152 conducted by FRV 'Walther Herwig III' do not indicate any improvements in state of the stocks, although no fishing effort was recently directed towards groundfish. The cod stock showed again a record low and is presently dominated by recruits of the year classes 1991 and 1993. Both year classes are considered to be weak and the cod stock is beyond the 'minimum biologically acceptable level'. Consequently, an increase in stock abundance is not expected either in short or long term. Other ecologically or economically important fish species, American plaice, redfish, wolffish and starry skate, were also found to have minimum stock abundances. By-catch estimates of juvenile groundfish taken by the shrimp fishery, operating at traditional grounds of cod and redfish fisheries, are indispensible. Analysis of climatological data from Nuuk/West Greenland indicates that climate during the past fourty years was characterized by two decades of anomalous warm conditions, and cooling which dominates the dimate since 1969. Anomalous cold events were encountered during 1983, 1984 and during 1992, 1993. Similar to the air temperature anomalies, autumn temperatures of the ocean surface layer indicate cold and warm periods during the past thirty years. In contrast to the colder than normal atmospheric conditions during the early nineties, however, the ocean conditions indicate intermediate warming.